F.L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney - Gill, Anthony C.; Russell, Barry C.; Nelson, Gary (Zootaxa, 2018)
Type specimens were located in the Macleay Museum for five species described by F.L. de Castelnau: Kurtus gulliveri (syntype), Pseudoambassis macleayi (lectotype and two paralectotypes), Pseudoambassis elongatus (lectotype and paralectotype), Acanthoperca gulliveri (syntype) and Engraulis nasutus (syntypes). The last-named is shown to be a senior subjective synonym of Anchovia aestuaria Ogibly 1910, and is referred to the genus Thryssa Cuvier 1829.